Pusaran Konflik Agraria Dan Model Resolusi Konflik Berbasis Keadilan Restoratif - Nurnaningsih, Nurnaningsih (UI Scholars Hub, 2022)
Land acquisition for public purposes does not really provide a solution for the National Strategic Project (PSN). Many land conflicts continue to occur as a result of this. The construction of the Bener Dam in Wadas Village, Bener District, Purworejo Regency, Central Java Province is one of the conflicts over the PSN. For that we need a solution that guarantees justice and legal protection for the people in Indonesia.